HUBUNGAN TINGKAT KONSUMSI IKAN LAUT TERHADAP KADAR MERCURY DALAM RAMBUT DAN KESEHATAN NELAYAN DI PANTAI KENJERAN SURABAYA - Sudarmaji, Sudarmaji (Jurnal Teknologi Lingkungan, 2004)
Surabaya Kenjeran Beach, as a part of Eastern coastal area at East Java, in addition to has function as a sea recreation (a tour) place and fishing, it also estuary for community channel and rivers from city. The condition of Surabaya Kenjeran Beach effected by Hg pollution, had observed by previous researcher, they suggested that water, sediment, and fishes from Kenjeran Beach were already dirtied by Hg at dangerous level. Hg that can be found in industrial waste generally has a inorganic form, but in the water environment, inorganic Hg change into organic Hg by microorganism (for example, methyl Hg) which is more toxic. Fisherman communities is one of the group which have a risk getting effect of methyl Hg, because they usually eat fish from sea that dirtied by Hg.This research plan is case control, in order to studying relations between consumed sea fish and degree of Hg in fisherman’s hair, measuring average degree of Hg in their hair and than compare it with limit value, and also studying healthy disorder sigh that likely appear as a result of Hg poisoning. This research took place at Kenjeran district, Bulak sub district, Surabaya. The number of samples for group who affected by Hg are 70 person and controlled group are 45 person. Respondent’s hair (research subject) was taken and then observed by Atomic Absorption Spectrophotometer (AAS) No Flame.As result, at the fisherman group who consumed sea fish at average 99.11 g/day, they have degree of Hg in their hair is 256.086 ppb. There are no data of consume sea fish at that time for the controlled group, average degree of Hg in their hair is 0.511 ppb. Healthy disorder sigh (subjective symptoms) which is suspicious as a result of Hg poisoning at this research are kidney, lever disorder, headache, painful, tremor, bleeding gums, and visual disorder.Conclusion is, statistically there is significantly relations between consumed sea fish and degree of Hg in hair, and average degree of Hg in the effected group’s hair is higher than the controlled group, but it’s not over limit value that recommended by National Research Council (NRC) is 12 ppm, also there is significantly relations between degree of Hg in hair and healthy disorder sigh (subjective symptoms).